2021
DOI: 10.1038/s41598-021-94505-w
|View full text |Cite|
|
Sign up to set email alerts
|

Caste development and sex ratio of the Ryukyu drywood termite Neotermes sugioi and its potential mechanisms

Abstract: Sex allocation is one of the most studied traits in evolutionary biology because its theoretical predictions match the empirical data. Here, using the Ryukyu dry-wood termite Neotermes sugioi, we investigated several factors that could bias the sex allocation in three populations (Okinawa, Ishigaki/Iriomote, and Yonaguni). Our survey showed that there were more queen-only colonies than king-only colonies in these populations, suggesting a longer lifespan of the queens than that of the kings. In this condition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…on these results, one can predict an equal numerical sex ratio in the Ishigaki population. However, Miyaguni et al (2021) showed male-biased numerical sex ratios in older developmental stages (pseudergates, nymphs, alates) both in Okinawa and Ishigaki populations. One hypothesis to solve this discrepancy is the annual and seasonal variation in the primary sex ratio of the Ishigaki population.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…on these results, one can predict an equal numerical sex ratio in the Ishigaki population. However, Miyaguni et al (2021) showed male-biased numerical sex ratios in older developmental stages (pseudergates, nymphs, alates) both in Okinawa and Ishigaki populations. One hypothesis to solve this discrepancy is the annual and seasonal variation in the primary sex ratio of the Ishigaki population.…”
Section: Discussionmentioning
confidence: 91%
“…4.0.2 (R Development Core Team 2020) was used for analyses. We also analyzed the correlation between the presence of a neotenic king and the colony-level sex ratio in N. sugioi, using the previously published field data on the reproductive structure and sex ratios of pseudergates in Okinawa population from May to August (Miyaguni et al, 2021). The data included colonies with a neotenic king and a primary queen (7 colonies).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…obs .). To date, evidence of detection and avoidance of nestmate pairings are scarce and inconsistent in termites 12 , 37 , 38 . Inbreeding avoidance can occur through a split sex ratio between colonies, or differences between the sexes in their dispersal range or in their timing of emergence 39 .…”
Section: Discussionmentioning
confidence: 99%